Is there a relationship between ovarian reserve and blood groups in infertile patients? - Kan, Ozgur; Gorkem, Umit; Alkilic, Aysegul; Taskiran, Deniz; Kocak, Ozgur; Yildirim, Engin; Togrul, Cihan (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Evaluation of ovarian reserve in infertile patients had become an important concept in assisted reproductive techniques (ART) success work-up. Recent studies reported an association between blood type and ovarian reserve. Therefore, the aim of this study was to analyze the relationship between blood type and ovarian reserve in infertile patients. Study Design: In this retrospective, observational and single-center study, a total of 311 women who were applied for fertility seek between January 2018 and November 2018 were included. As a threshold of ovarian reserve, - serum follicle stimulating hormone levels (>10 mLU/mL) and antral follicle counts (≤5) at early follicular phase were taken to reflect diminished ovarian reserve (DOR). The main outcome was the association between blood types and ovarian reserve. Secondary outcomes were biochemical and clinical pregnancy rates. Results: There was no relationship between blood types and follicle stimulating hormone levels (FSH). Elevated FSH levels were associated with only age and antral follicle count. Similar to the results of ovarian reserve, biochemical and clinical pregnancy outcomes are not affected by blood groups and Rhesus factor. Conclusion: Patients’ blood type did not have any impact on ovarian reserve. In addition, neither blood type nor rhesus factor have an effect on predicting pregnancy outcomes in ART patients.